Optimization of biometric recognition using cuckoo search algorithm: a preliminary version for minutia based fingerprint identification - Thangamanimaran, Dhileepan; Chandar, M. Sharat; Chandia, S. (International Journal of Engineering and Technology, 2017)
Currently Behavioural Biometrics is the most widely used means of security.Â  Though Behavioural Biometrics is highly reliable and secure, the data handling process is quite complex. This Problem can be solved by optimizing the process using cuckoo search algorithm.This Paper seeks to optimize the process of fingerprint matching by using an optimal algorithm. The Minutiae in the form of a matrix is extracted from a fingerprint. The Matrix is then split into smaller matrices with increasing dimension and then compared. The matrix with least dimension it is matched. If the Match is true then the verification of next generation bigger matrix is done. If the Match tends to be false then the matrix is skipped and the process is continued for the next matrix in the database. The Process is repeated until accurate match is obtained.Though the time reduced by the optimization of the finger print matching algorithm is insignificant for a smaller data set such as finger print data, it can be a key factor when a larger set of Behavioural biometrics data is considered.